Cover Feature: Reductant‐Induced Free Radical Fluoroalkylation of Nitrogen Heterocycles and Innate Aromatic Amino Acid Residues in Peptides and Proteins (Chem. Eur. J. 69/2019). Issue 69 (31st October 2019) - Rahimidashaghoul, Kheironnesae; Klimánková, Iveta; Hubálek, Martin; Korecký, Michal; Chvojka, Matúš; Pokorný, Daniel; Matoušek, Václav; Fojtík, Lukáš; Kavan, Daniel; Kukačka, Zdeněk; Novák, Petr; Beier, Petr
Abstract : In an underwater sea scene, the key process of protein functionalization on tryptophan is shown. The follow‐up click reaction by using the pink reagent carrying a payload delivers the conjugate of choice. Realistic depiction of hypervalent iodine reagents includes the T‐shape geometry on the iodine atom and the azido‐containing fluoroalkyl group. On the seabed there are side products from the reagent after the reaction with the protein. More information can be found in the Full Paper by P. Novák, P. Beier, et al. on page 15779 .